Double force. Applying indicators and qualitative measuring to the public library learning space - von Krogh, Petter; Røgler , Jannicke (BIBLIOPOLIS, 2020)
Norwegian statistics generally maintain a high standard. Statistics Norway, is responsible for coordinating all official statistics in Norway. The actual collecting of library statistics, is handled by the National Library of Norway. The demand for detailed statistics from the library community has been low, but this is slowly changing. In Norway, the county libraries serve as development agencies for public and school libraries in their region. At Buskerud County Library, we believe that to guide and support development as efficient as possible, we have to measure it. The quantitative values offered by national statistics are weighted towards traditional library operations. This means that they barely touch upon the role of public libraries as learning arenas, which has been our main focus in this project. Buskerud County Library seek to improve the public library as a learning space. In order to measure the level and quality of change, we adopted and customized a well-known talent management tool, called the Performance-Potential Matrix. The result was the Buskerud Measuring Model. Testing our model, we discovered that the numeric results relied too much on the qualitative descriptions used in the process. We knew we needed to integrate more quantitative data in the measuring process if we were to raise the quality of the test results. By combining our qualitative definitions with the quantitative data of the national statistics and indicators, we will get a better and more extensive knowledge base to support a continuous development of the library. This paper describes the use of the Buskerud Measuring Model on public library as a learning arena, and discusses how to implement the national statistics and indicators into the process.